Zirconia toughened mica glass ceramics for dental restorations. Issue 3 (March 2018) - Gali, Sivaranjani; K., Ravikumar; Murthy, B.V.S.; Basu, Bikramjit
Highlights: YSZ of 5, 10, 15 & 20 wt.% to mica glass has been heat treated to achieve clinically relevant mechanical properties for dental restorations. Microstructure reveals fluorophlogopite as the predominant phase. YSZ presents as non-reactive and appears as agglomerates in the glass matrix. YSZ plays a role in influencing mechanical properties of mica glass ceramics without compromising their brittleness index & chemical solubility. Abstract: Objective: The objective of the present study is to understand the role of yttria stabilized zirconia (YSZ) in achieving the desired spectrum of clinically relevant mechanical properties (hardness, elastic modulus, fracture toughness and brittleness index) and chemical solubility of mica glass ceramics. Methods: The glass–zirconia mixtures with varying amounts of YSZ (0, 5, 10, 15 and 20 wt.%) were ball milled, compacted and sintered to obtain pellets of glass ceramic-YSZ composites. Phase analysis was carried out using X-ray diffraction and microstructural characterization with SEM revealed the crystal morphology of the composites. Mechanical properties such as Vickers hardness, elastic modulus, indentation fracture toughness and chemical solubility were assessed. Results: Phase analysis of sintered pellets of glass ceramic-YSZ composites revealed the characteristic peaks of fluorophlogopite (FPP) and tetragonal zirconia. Microstructural investigation showed plate and lath-like interlocking mica crystals with embedded zirconia. Vickers hardness of 9.2 GPa, elastic modulus of 125 GPa, indentation toughness of 3.6 MPa·m 1/2, and chemical solubility of 30 μg/cm 2 (well below the permissible limit) were recorded with mica glass ceramics containing 20 wt.% YSZ. Significance: An increase in hardness and toughness of the glass ceramic-YSZ composites with no compromise on their brittleness index and chemical solubility has been observed. Such spectrum of properties can be utilised for developing a machinable ceramic for low stress bearing inlays, onlays and veneers.